Gossypitrin, A Naturally Occurring Flavonoid, Attenuates Iron-Induced Neuronal and Mitochondrial Damage - María Ángeles Bécquer-Viart; Adonis Armentero-López; Daniel Alvarez-Almiñaque; Roberto Fernández-Acosta; Yasser Matos-Peralta; Richard F. D’Vries; Javier Marín-Prida; Gilberto L. Pardo-Andreu (Molecules, 2021)
The disruption of iron homeostasis is an important factor in the loss of mitochondrial function in neural cells, leading to neurodegeneration. Here, we assessed the protective action of gossypitrin (Gos), a naturally occurring flavonoid, on iron-induced neuronal cell damage using mouse hippocampal HT-22 cells and mitochondria isolated from rat brains. Gos was able to rescue HT22 cells from the damage induced by 100 µM Fe(II)-citrate (EC50 8.6 µM). This protection was linked to the prevention of both iron-induced mitochondrial membrane potential dissipation and ATP depletion. In isolated mitochondria, Gos (50 µM) elicited an almost complete protection against iron-induced mitochondrial swelling, the loss of mitochondrial transmembrane potential and ATP depletion. Gos also prevented Fe(II)-citrate-induced mitochondrial lipid peroxidation with an IC50 value (12.45 µM) that was about nine time lower than that for the tert-butylhydroperoxide-induced oxidation. Furthermore, the flavonoid was effective in inhibiting the degradation of both 15 and 1.5 mM 2-deoxyribose. It also decreased Fe(II) concentration with time, while increasing O2 consumption rate, and impairing the reduction of Fe(III) by ascorbate. Gos–Fe(II) complexes were detected by UV-VIS and IR spectroscopies, with an apparent Gos-iron stoichiometry of 2:1. Results suggest that Gos does not generally act as a classical antioxidant, but it directly affects iron, by maintaining it in its ferric form after stimulating Fe(II) oxidation. Metal ions would therefore be unable to participate in a Fenton-type reaction and the lipid peroxidation propagation phase. Hence, Gos could be used to treat neuronal diseases associated with iron-induced oxidative stress and mitochondrial damage.